The effect of utilising digital Quran on intrinsic motivation and Quranic memorisation among tahfiz students - Ismail, Halim; Mohammad, salamiah (2023)
This study aims to identify the effect of utilising the digital Quran on intrinsic motivation and Quranic memorisation among 150 students from al-Hidayah Tahfiz Academy Kuala Lumpur, Malaysia. This study employed a quantitative study, and the main instrument utilised was a questionnaire given to the 150 participants. The data were analysed using descriptive analysis. The findings show that the Digital Quran intrinsically motivates tahfiz students to learn and improve in memorising Qur’an. Students with good skills perceive learning with Digital Quran as easy and fun, giving them happiness and enjoyment in the classroom. This study impacts tahfiz students and boosts their interest in using Digital Quran in their learning.